Hotel Supervisor Incivility and Its Effects on Employee Productivity and Turnover Intention: The Mediating Role of Ego Depletion - Lacap, Jean Paolo; Fadrigalan, Joe Mari; Eser, Edgie; Maigue, Mach Ronald; Mabulay, Princess Airene (The South East Asian Journal of Management, 2025)
Research Aims: This study examines the influence of supervisor incivility on hotel employees’ productivity and turnover intention, and further investigates the mediating role of ego depletion in these relationships. Design/Methodology/Approach: Participants were hotel employees (N = 300) who were selected using snowball sampling. A predictive research design and partial least-squares path modelling were used to gauge the propositions of the study. Research Findings: The results indicate that supervisor incivility has a significant impact on ego depletion, employee productivity, and turnover intention. Ego depletion was found to have a substantial effect on both employee productivity and turnover intention, and served as a mediating factor between supervisor incivility and turnover intention, but not in the relationship between supervisor incivility and employee productivity. Theoretical Contribution/Originality: This study utilized the SOR model to show how rude behaviour from a boss can impact how employees work and their desire to leave the job. This occurs through a process known as ego depletion. The model helps to explain how a boss's rudeness influences employees’ decisions and actions. Managerial Implication in the South East Asian Context: The findings of this study indicate that when supervisors exhibit incivility, hotel employees may experience rising ego depletion, thus affecting productivity and leading to increased turnover intentions. Such incivility in the hotel environment can ultimately diminish the service quality and heighten guest dissatisfaction. Research Limitation & Implications: This study highlights the need for organizations to foster respectful and supportive supervisor–employee relationships and to promote a positive work environment that safeguards employee well-being and enhances performance. However, the respondents were drawn exclusively from the National Capital Region of the Philippines.